2017
DOI: 10.18332/tpc/70277
|View full text |Cite
|
Sign up to set email alerts
|

Standardized packaging and illicit tobacco use: A systematic review

Abstract: INTRODUCTION To systematically review the evidence regarding the effect of standardized packaging on illicit tobacco use. METHODS Data sources were EMBASE, Web of Knowledge, Scopus, PsycInfo, Medline, and the British Library catalogue, from 01/01/1987 to 28/11/2016. Reference lists of included studies were hand searched for additional papers. Search strategies were based on the terms 'tobacco', 'packaging' and 'illicit'. The search was restricted to English language references. Two reviewers screened titles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Research exploring perceptions and use of tobacco and nicotine products not covered by plain packaging, where applicable, is also important. While a potential increase in illicit tobacco use as a result of plain packaging has been central to industry opposition to this policy, the impact on illicit tobacco use has received limited attention 75. Although research suggests neither the availability nor use of illicit tobacco has changed,76–78 research on illicit use outside of Australia is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Research exploring perceptions and use of tobacco and nicotine products not covered by plain packaging, where applicable, is also important. While a potential increase in illicit tobacco use as a result of plain packaging has been central to industry opposition to this policy, the impact on illicit tobacco use has received limited attention 75. Although research suggests neither the availability nor use of illicit tobacco has changed,76–78 research on illicit use outside of Australia is needed.…”
Section: Introductionmentioning
confidence: 99%
“…This study is in contrast to tobacco industry claims that standardised packaging would increase the use of illicit tobacco. A systematic review in 2017 found no evidence that standardised packaging was linked to increased illicit trade in ten included studies [8]. There was no evidence of an increase in illicit tobacco purchasing in relation to standardised packaging in Australia which was the first country to implement such legislation in 2012 [16] though this study used different methodology where illicit products were based on brands and product details rather than place of purchase.…”
Section: Discussionmentioning
confidence: 84%
“…Prior to implementation, the tobacco industry argued that implementation of standardised packaging would lead to a substantial increase in illicit tobacco sales [6,7]. Their main argument was that it would be easier to counterfeit standardised packaging and therefore the illicit products will be cheaper and easier to access though no specific estimates of illicit market changes were provided [8]. Tobacco tax increases are intended to increases the cigarette prices and in turn encourage smoking cessation.…”
Section: Introductionmentioning
confidence: 99%
“…The tobacco industry has opposed plain packaging based on the key argument that it will increase the illicit tobacco trade (Lie et al, 2018;Crosbie et al, 2019;Gallagher et al, 2019). However, research evidence does not substantiate this argument (Joossens, 2012;Evans-Reeves et al, 2015;Scollo et al, 2015b;Haighton et al, 2017). Additionally, post-implementation studies in countries that have implemented plain packaging have shown that it has contributed to the reduction of smoking prevalence and facilitated the easier identification of illicit cigarettes from other countries (Brennan et al, 2015;Durkin et al, 2015;Scollo et al, 2015a;Wakefield et al, 2015).…”
Section: Introductionmentioning
confidence: 99%